Exploring the impact of CAATs adoption on audit quality: A TOE framework approach - Emily, Lindsay Carnelian; Sujanto, Kimberly Adeline; Angelus, Michael (Edelweiss Applied Science and Technology, 2025)
The rise of artificial intelligence and big data has compelled public accounting firms to integrate advanced technologies into their audit processes to handle the growing scale, diversity, and complexity of client data effectively. Drawing on the Technology-Organization-Environment (TOE) framework, this study analyzes how technological, organizational, and environmental contexts influence the adoption of Computer-Assisted Audit Techniques (CAATs) and evaluates their contribution to enhancing audit quality. This study analyzed data from 115 external auditors from public accounting firms in Indonesia, obtained through questionnaire distribution. The collected data were then processed using SMART-PLS 4.0, with a series of tests such as outer models, validity and reliability tests, determination coefficients, and hypothesis testing to analyze and interpret the research data. The study concludes that within the TOE framework, the technological and organizational contexts significantly influence the adoption of CAATs and positively impact audit quality, while the environmental context shows no significant effect. Strong technology and organizational support play a critical role in the effective implementation of CAATs to improve audit quality. By increasing management readiness and commitment, accounting firms can produce more efficient and reliable audit processes.